Systemic Corticosteroids for Inflammatory Disorders in Pediatrics - Cimaz, Rolando; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2015)
This comprehensive volume provides the current state of the art use of corticosteroids in the pediatric age group. The book consists of 14 chapters written by leading authors from around the world. The first chapters deal with historical notes, general concepts on treatment with corticosteroids with regard to indications and side effects, and the basic pharmacologic properties of these compounds. The rest of the book is devoted to the specific use of corticosteroids in the different pediatric subspecialties. Despite advances with newer effective immunosuppressive and anti-inflammatory drugs, corticosteroids still remain the mainstay of therapy for many disorders. Rolando Cimaz is Head of the Pediatric Rheumatology Unit at Meyer Children's Hopital in Florence, Italy, and is an Associate Professor of Pediatrics at the University of Florence, Italy. He graduated from Milan University in Italy in 1987, is a specialist in Pediatrics (1991) and in Rheumatology (2003), and did his Fellowship in Pediatric Rheumatology in Dallas, Texas, USA, in 1993-1994. He was Maitre de Conférences des Universités at Université Claude Bernard-Lyon in Lyon, France from 2005 to 2007. His main interest is pediatric rheumatology, and he has special expertise and scientific interest in osteoporosis, antiphospholipid antibodies, Kawasaki disease, synovial T cells, and neonatal lupus. Currently he is involved in many research projects, nationally and internationally. He has been on the Council of the Pediatric Rheumatology European Society from 1999 to 2005 (treasurer), and from 2014-present (Research Chair). He is a member of the American College of Rheumatology, the Italian Society of Pediatrics, and the French Society of Pediatric Inflammatory Diseases. He is co-author of more than 230 peer-reviewed articles on PubMed, as well as more than 20 book chapters, all in the field of pediatric rheumatology. He is, or has been, on the Editorial board of several international journals (Pediatric Rheumatology Online Journal, Lupus, Arthritis and Rheumatism) and co-edited the book "Systemic Autoimmune Diseases in Pediatrics.".
Systemic Corticosteroids for Autoimmune/Inflammatory Disorders in Children Introduction -- Corticosteroids in the Treatment of Childhood Rheumatic Diseases: An Historical Review -- Systemic Corticosteroids for Autoimmune/Inflammatory Disorders in Children -- The clinical pharmacology of past, present, and future glucocorticoids -- The molecular mechanisms responsible for the anti-inflammatory and immunosuppressive effects of glucocorticoids -- CORTICOSTEROIDS IN JUVENILE IDIOPATHIC ARTHRITIS -- Systemic Corticosteroids in Childhood Vasculitides -- Steroids in paediatric-onset SLE and other connective tissue diseases -- GLUCOCORTICOID IN PEDIATRIC GASTROINTESTINAL DISORDERS -- CORTICOSTEROIDS IN PEDIATRIC DERMATOLOGY -- Corticosteroids in pediatric endocrinology -- SYSTEMIC CORTICOSTEROIDS IN RESPIRATORY DISEASES IN CHILDREN -- Corticosteroids in Paediatric Nephrology -- Corticosteroids in neonatology: Postnatal corticosteroids in preterm infants with bronchopulmonary dysplasia (BPD).
Keywords: Pediatrics; Rheumatology; Pharmacotherapy; Pediatrics; Rheumatology; Pharmacotherapy